PERSEPSI SISWA KELAS XI TERHADAP PELAKSANAAN KEGIATAN PRAKTIK JURUSAN DESAIN PRODUK KREATIF KRIYA KAYU DI SEKOLAH MENENGAH KEJURUAN NEGERI 8 PADANG - ANDRE HARDIAN DELVINO, Drs. Erfizal, M.Pd. (Serupa The Journal of Art Education, 2019)
Student's perceptions on the implementation of practical activities Wood Craft DPK department,  which includes aspects; 1) The students 'perception of facilities and infrastructure workshops, 2)  students' perception of the preparation of the practice, 3) students 'perception of implementation of  the practices, 4) students' perception of the 4 closure of the practice . Which involves the student respondents as many as 48 people. This is a descriptive approach to quantitative research, using a perception questionnaire rating scale. The instrument has been tested using SPSS 16 with a correlation coefficient of 0.300 in the above figure. With data analysis using percentage figures.The results showed class XI student perceptions on the implementation of practical activities  department of Wood Craft enter. Both categories with a percentage value of 83.99%, with aspects: 1) students' perceptions of facilities and infrastructure workshops in the category of very good value percentage of 87.08%, 2) students' students' percentage with a percentage of 81.94%, 3)  students' students 'The implementation of closure is a percentage of the value of 86.07%.Based on the findings, students' perception of enforcement activity Wood Craft pact department at SMK N 8 Padang rated good (83.99%), with an aspect; 1) the perception of a very good  infrastructure (87.08%), 2) the preparation of good practice (81.94%), 3) the perception of  implementation of good practice (82.37%), and 4) the perception closure excellent practice (86.07%).Keywords: Perceptions of students, learning practices